Histopathology findings in patients presenting with menorrhagia: A study of 100 hysterectomy specimen - Nilima G Sawke (Journal of Mid-Life Health, 2015)
Background: Menorrhagia, by definition, is heavy cyclical blood loss in excess of 80 ml/month of menstrual period lasting longer than 7 days. There are many possible causes of heavy menstrual bleeding which include hormonal imbalance, fibroids, miscarriage or ectopic pregnancy, nonhormonal intrauterine device, adenomyosis, pelvic inflammatory disease, and rarely uterine, ovarian, or cervical cancer. Treatment depends on the causes of the menorrhagia. Hysterectomy is one of the several surgical procedures as definitive treatment. Objective: To determine the histopathologic spectrum of lesions associated with menorrhagia in different age groups. Study Design: This prospective descriptive study was conducted at the Department of Pathology, People′s College of Medical Sciences and Research Centre, Bhopal. During the study period, 100 hysterectomy specimens were taken which were performed for the treatment of menorrhagia. Patients with menorrhagia in the age group of 30-50 years were selected after detailed history and fulfilling the inclusion criteria. Result: In our study, it was observed that maximum number of cases were in the age group of 41-50 years (n = 35) followed by the age group of 31-40 (n = 30). Out of 100 cases, 31% cases (n = 31) showed adenomyosis followed by leiomyomas 25% (n = 25), endometrial hyperplasia 23% (n = 23), and endometrial polyp 4% (n = 4). 11% cases (n = 11) showed dual pathology consisting of both adenomyosis and endometrial hyperplasia and 6% cases (n = 6) of leiomyoma with adenomyosis. Conclusion: Uterine adenomyosis and leiomyoma are the most common benign conditions found in hysterectomy specimens with peak incidence at 31-50 years. Patients having menorrhagia above 40 years should be screened for any endometrial pathology. Histopathology is mandatory for confirming diagnosis and the key to effective therapy and optimal outcome.